Quality Assurance in Guava (Psidium guajava L.) Production: Literature Review - López Valle, Isela Janeth (2026)
Quality assurance (QA) in the agri-food sector represents a set of practices aimed at ensuring a high level of quality in guava (Psidium guajava L.) production. The objective of this research is to review recent studies on quality assurance systems and strategies applied to guava production, with a particular focus on Mexico. A literature review was conducted using databases such as SCOPUS, Redalyc, Springer, and SciELO, considering publications from the last ten years. This review was complemented by a survey administered to guava prodicers in the municipality of Benito Juarez, Michoacan. Out of 113 collected articles, 20 were selected for detailed analysis. The findings indicate that guava quality assurance is largely influenced by the implementation of systems such as ISO 22000 and Hazard Analysis and Critical Control Points (HACCP). The study also identifies regional differences in infrastructure and access to certifications as jey determinants of quality levels. Moreover, the reviewed literature highlights advancements in postharvest tecnologies, artificial intelligence, and natural coatings that contribute to improved product preservation. Finally, this article presents a comprehensive literary analysis on the topic, addressing a research gap previously unexplored.